Evaluation of Regional Government Policy in Handling Beggars in Banyumas (Study on Beggars on the Krumput Route, Kemranjen District) - Silvia Amanda Putri; Nidya Ayu Wulandari Ramdan (Department of Public Administration, University Wijaykusuma Purwokerto, 2026)
Poverty is a social problem that is often found in society. One of the causes of the high poverty rate is beggars. Banyumas Regency as the policy maker has made efforts to address this problem by establishing Regional Regulation Number 16 of 2015 concerning the Management of Social Diseases, but beggars on the Krumput Route are a real case of the persistence of beggars in Banyumas Regency after the Regional Regulation was enacted. This study uses a qualitative descriptive method with data obtained through observation, interviews, and documentation. The purpose of this study is to describe and analyze the evaluation of local government policies in dealing with beggars in Banyumas (a study of beggars on the Krumput Route, Kemranjen District). The results of the study refer to William N. Dunn's 6 Evaluation aspects, which show that in terms of effectiveness, the policies made have not been able to reduce the number of beggars on the Krumput Route, in terms of efficiency, there are limitations in the human resources involved, while in terms of adequacy, there is a problem, namely the support provided by the Regional Government. In terms of policy equality, it has not been implemented comprehensively. Meanwhile, in terms of responsiveness, there is a problem, namely that there are no complaints received regarding beggars on the Krumput route to the Regional Government, while in terms of the accuracy of the policies that have been implemented, they are general and not specific to the problems that exist on the Krumput Route. Therefore, the government is expected to be able to develop specific programs for the Krumput Route, improve the quality and quantity of human resources involved, solutions that involve collaboration between related parties, consistent and intensive control and socialization regarding complaint stalls to increase active community participation.